Spatial distribution analysis and risk factors for stunting in Kerinci Regency, Jambi Province Indonesia - Rd. Halim; Muhammad Syukri; Guspianto Guspianto; Fajar Akbar (AcTion: Aceh Nutrition Journal, 2023)
There are variations in the prevalence of stunting cases at the village level in Kerinci Regency. There have been no studies on the spatial distribution and risk factors of stunting cases in Kerinci Regency. This study aimed to determine the risk factors and spatial distribution of stunting. This research was conducted in Kerinci Regency from March to November 2020 using a case-control design and a total sampling technique. The study participants consisted of 223 patients and 223 controls. Children who experienced stunting were recorded at the health office. The controls were non-stunted children with an age range (±3 months) and sex who came from the same village as the cases—data collection through interview techniques and observation of the Mother and Child Health book. The chi-square test, logistic regression, and spatial distribution analysis were performed using the open-source software SatScan 10,1 and ArGIS 3,30. The analysis shows stunting cases clustered in Kayu Aro, Gunung Tujuh, and Keliling Danau Districts. A low father's education level (aOR=1,76), father's height <161 cm (aOR=1,52), mother's height <150 cm (aOR=1,83), and incomplete immunization status (aOR=1,6) were risk factors for stunting. In conclusion, cases of stunting clustered in three sub-districts, and the leading risk factor was the mother's height. The health office should make specific intervention efforts before and during pregnancy and focus on cluster-indicated areas.